Training cosmetology students in Arkansas to help dermatologists find skin cancers earlier: results of a cluster-randomized controlled trial. (28th July 2020) - Fischbach, Lori; Faramawi, Mohammed F; Girard, Deborah; Thapa, Susan; Travers, Robin
Abstract: Background: We tested an educational video in cosmetology schools to increase students' knowledge about skin cancer, sun-safety practices, identifying suspicious lesions and recommending clients consult a dermatologist when a suspicious lesion is observed. Methods: We used a cluster-randomized controlled study design to randomize 22 cosmetology schools to receive our educational video or a publicly accessible healthy lifestyle video (control). Results: Students who received the intervention were more likely than controls to increase their knowledge of skin cancer, risk factors and how to identify potential skin cancers (risk ratio [RR] and 95% confidence interval = 2.86 [1.58–5.20]). At follow-up, students in the intervention group were more likely than those in the control group to look for suspicious moles on their clients' faces, scalps and necks (RRs = 1.75, 2.16 and 2.90, respectively). Additionally, students in the intervention group were more likely to communicate with clients about sun-safety practices (RR = 1.74 [1.11–2.73]) and consulting a dermatologist about suspicious moles (RR = 1.57 [1.03–2.41]). Conclusions: Our educational video helped cosmetology students recognize potential skin cancers and talk with clients about sun safety and consulting a dermatologist about suspicious moles. Such videos may play a role in the public health surveillance of skin cancers in communities.